2013
DOI: 10.1016/j.surg.2013.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Physician follow-up and observation of guidelines in the post treatment surveillance of colorectal cancer

Abstract: Background Guidelines for post resection surveillance of colorectal cancer recommend a collection of the patient's history and physical examination, testing for carcinoembryonic antigen (CEA), and colonoscopy. No consistent guidelines exist for the use of abdominal computed tomography (CT) and position emission tomography (PET)/PET-CT. The goal of our study was to describe current trends, the impact of oncologic follow-up on guideline adherence, and the patterns of use of nonrecommended tests. Methods We use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
21
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 32 publications
0
21
0
Order By: Relevance
“…Race, age and marital status had no effect. Vargas and colleagues 32 found that among 12,381 patients from the Texas Cancer Registry who were recurrence free for 3 years, 75.3% received at least one colonoscopy in a 3-year surveillance period. Salloum and colleagues 33 found that among 2297 patients, only 55.0% received one complete exam of the colon during the 18 months after treatment with curative intent.…”
Section: Discussionmentioning
confidence: 99%
“…Race, age and marital status had no effect. Vargas and colleagues 32 found that among 12,381 patients from the Texas Cancer Registry who were recurrence free for 3 years, 75.3% received at least one colonoscopy in a 3-year surveillance period. Salloum and colleagues 33 found that among 2297 patients, only 55.0% received one complete exam of the colon during the 18 months after treatment with curative intent.…”
Section: Discussionmentioning
confidence: 99%
“…Specialist care may improve guideline adherence, but the increased use of tests is perhaps a function of differential access to health care resources. 21,22 In our study, Ͼ 80% of the patients who had visited a medical oncologist after surgery had undergone a PET scan, and these patients were more likely to have undergone an early postsurgery scan. Also, patients who had visited a medical oncologist postsurgery and had received chemotherapy were greater than six times more likely to have undergone a PET scan compared with patients who had not visited a medical oncologist postsurgery or received chemotherapy.…”
mentioning
confidence: 61%
“…It is possible that advanced imaging studies performed within 6 months after surgery were done so for postoperative complications rather than for surveillance. 20,21 However, there is no role for PET in evaluating postoperative complications. Although these early PET scans could have been performed to establish a postsurgical baseline, there is no established role for early postoperative imaging in the routine care of patients with CRC who had been preoperatively staged.…”
mentioning
confidence: 99%
“…CEA is a tumor marker especially overexpressed in colorectal cancer, and there are many contradictory findings about sensitivity and usefulness of this tumor marker. It must be consider that assessment of CEA levels in serum has a major role in following and monitoring of patients for relapse after intended therapeutic program of CRC [8,10]. But there are several reports about unspecific elevated levels of CEA in apparently healthy smokers and elderly individuals or in some benign conditions such as liver and gastrointestinal system inflammations of any cause.…”
Section: Discussionmentioning
confidence: 99%